Potensi Desa Wisata di Desa Kuok Kecamatan Kuok Kabupaten Kampar - Angga Pramana; Esty Octiana Sari; Pebriandi Pebriandi; Irman Tinjo; Meta Riana Akma (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Belimbing Island Tourism Village is one of the tourist attractions located in kuok district kampar regency. Belimbing Island Tourism Village has great potential as a tourist attraction because of its natural cultural and indigenous values. Preserving and developing culture is a step that must be taken in order to maintain its cultural sustainability and can be felt by all people because cultural values are inseparable from the role of human beings as cultural beings who inherit the culture. This research aims to empower and develop the potential in Kuok Subdistrict, Kampar. The research method is descriptive qualitative. Data collection techniques using observations and interviews. Analysis is data reduction, data presentation and conclusion drawing. The results of this study are empowering and developing tourism potential in Belimbing Island is done by preserving it by studying the culture of Kuok Village through community leaders, adding to the beauty of the traditional home environment, and following community cultural activities that strengthen the sense of brotherhood.